PERCEIVED INFORMATION SECURITY, INFORMATION PRIVACY, RISK AND INSTITUTIONAL TRUST ON CONSUMER’S TRUST IN E-COMMERCE - Parengkuan, Frane Maorets (Universitas Sam Ratulangi, 2014)
E-commerce is widely being used in nowadays generation where the business entrepreneur from small to large institution, has widely taken advantage on the internet to promote business and deliver information about their product. Consumer trust is an important aspect of e-commerce, and understanding its antecedents and consequences is a prime concern. This research designed to find out the influence of Perceived Information Security, Privacy, Risk and Institutional Trust on Consumers Trust in E-Commerce at Manado. The location of this research took place in Manado and focused on the people who do online shopping or e-banking as their tools. The method used to analyze the data is the Multiple Regression Analysis which enables the researcher to analyze the influence of the independent variables to the dependent variable, which is Consumer Trust in E-commerce. The independent variables in this research are Perceived Information Security, Information Privacy, Risk and Institutional Trust. While the sample size are 100 respondents who have ever buy or exchange product thru internet. The result of this research shows that there is significant simultaneous and partial influence of Perceived Information Security, Privacy, Risk and Institutional Trust on Consumers Trust in E-commerce. Therefore, to enhance the Consumer Trust in E-commerce at Manado these are the proponents should be considered intensively. Keywords: perceived information security, consumer trust, e-commerce